Fortifikasi Cilok dengan Tepung Tulang Ikan Tenggiri sebagai Sumber Kalsium Alternatif - Hafidh Arkananta; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
This study aims to utilize mackerel fish bone waste as an additive in the production of cilok, a traditional tapioca-based snack, to enhance its calcium content. An experimental method was employed by fortifying the cilok dough with mackerel fish bone flour. The research process involved preparing the fortified cilok, observing the production process and product characteristics, and conducting a hedonic test to evaluate consumer acceptance. The hedonic test was carried out with 100 respondents who assessed attributes such as color, aroma, texture, and taste. The results showed that the addition of mackerel fish bone flour at certain proportions was acceptable to the panelists in terms of organoleptic qualities, including color, aroma, texture, and taste. This study demonstrates that fortifying traditional flour-based foods with fish bone waste has the potential to be an innovative solution for improving nutritional value, particularly calcium content, while also contributing to the sustainable utilization of marine-based food waste.